Natural Killer Cells Induce CD8+ T Cell Dysfunction via Galectin-9/TIM-3 in Chronic Hepatitis B Virus Infection - Liu, Siyu; Xu, Chang; Yang, Fan; Zong, Lu; Qin, Yizu; Gao, Yufeng; Su, Qian; Li, Tuantuan; Li, Ye; Xu, Yuanhong; Zheng, Meijuan (Frontiers in Immunology, 2022)
The antiviral response of natural killer (NK) cells and CD8+ T cells is weak in patients with chronic hepatitis B (CHB) infection. However, the specific characteristics of these cells and the association between NK cells and CD8+ T cell dysfunction is not well known. In this study, higher galectin-9 (Gal-9) expression was observed in circulating NK cells from CHB patients than from healthy controls and was found to contribute to NK cell dysfunction. In addition, circulating CD8+ T cells showed obvious dysfunction and overexpressed TIM-3, the natural receptor of Gal-9, during active CHB infection. Gal-9+ and Gal-9- NK cells from active CHB patients were sorted and cocultured with autologous CD8+ T cells. The proportion of tetramer+CD8+ T cells and the cytokines production of CD8+ T cells were lower after cocultivation with Gal-9+ than with Gal-9- NK cells. We showed that in vitro depletion of NK cells increased circulating hepatitis B virus (HBV)-specific CD8+ T cell responses in patients with active CHB infection. Because Gal-9 is increased in the serum of CHB patients, CD8+ T cells were sorted and cultured with exogenous Gal-9, resulting in lower IFN-g, TNF-a, CD107a, and granzyme B levels, decreased expression of the activation receptor CD69, increased expression of TIM-3, and a high percentage of early apoptotic CD8+ T cells. Blocking Gal-9 or TIM-3 in vitro in a culture of peripheral blood mononuclear cells (PBMCs) stimulated with HBV peptide from active CHB patients restored CD8+ T cell function. However, blocking Gal-9 in vitro after removal of NK cells from PBMCs did not rescue CD8+ T cells exhaustion. Furthermore, NK and CD8+ T cells from active CHB patients were sorted and cocultured in vitro, and the exhaustion of CD8+ T cells were alleviated after blocking Gal-9 or TIM-3. In summary, overexpression of Gal-9 on NK cells, which interacts with TIM-3+CD8+ T cells and likely contributes to antiviral CD8+ T cell dysfunction, may be a potential target for the treatment of CHB patients.